Pain Level of Postoperative Orthopedic Patients at Dr. Soetomo General Hospital - David Wicaksono; Lilik Herawati; Herdy Sulistyono (Indonesian Journal of Anesthesiology and Reanimation, 2019)
Introduction: Postoperative pain is the most undesirable consequence of the surgery. If it is not managed properly, it can lead to a long healing. However, assessment and treatment of postoperative pain in surgical wards still have not received attention. Differences in patient's pain level after surgery and after being transferred to the surgical ward is very important in monitoring the effectiveness postoperative pain management. Objective: This study was conducted to determine the overview of pain level experienced by patients following orthopedic surgery and to know the individual factors that can affect the patient's pain level. Method and Material: This research was observational analytic with 43 orthopedic postoperative patients as a sample. The Patients' pain level was measured by the Numeric Rating Scale (NRS) at one hour after surgery and 24 hours after surgery. Result and Discussion:The Pain level one hour after surgery varied between pain level 0 as much as 53% to pain level 8 as much as 4.7%. The results of measurements of pain 24 hours after surgery only 23.3% of the patients who did not complain of pain, and there was a patient who experienced pain level 10. The results of the statistical calculation, the difference between the level of pain one hour and 24 hours post-surgery obtained value of p=0.037 (p<0.05). Conclusion: There was a significant difference between the pain level at one hour and 24 hours post-surgery. It might be due to the process of peripheral and central sensitization in patients with delayed pain management. It also may be influenced by individual factors as well as medical personnel.